Which Factors Determine the Utilization of Preferential Tariff Rates? - Piotr Lukaszuk; Stefan Legge (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The number of bilateral and multilateral trade agreements has surged in recent years. In order to benefit from preferential tariff rates,firms must apply and comply with rules of origin requirements. This is costly and explains why preference utilization rates (PUR) are far below 100 percent. In this paper, we examine the variation in PUR both across products and countries of origin. This allows us to analyze determinants of utilization rates as well as the costs associated with using a preferential trade agreement. Our findings highlight that both savings potential and trade volume positively affect utilization. Furthermore, the product mix that two countries trade has substantial predictive power for the overall utilization rate.
Keywords: F13; F14; 330; FTA; RTA; Tariffs; Trade Policy; Utilization